Determination of normal concentration levels of Cd, Pb, Hg, Cu, Zn and Se in urine of the population in the Czech Republic - Benes, B; Spĕvácková, V; Smíd, J; Cejchanová, M; Kaplanová, E; Cerná, M; Gajewská, V; Blatný, J (Central European journal of public health, 2002)
Knowledge of normal levels of concentrations of trace elements (Cd, Pb, Hg, Cu, Zn, and Se) in the population serves, among others, in design of regulations concerning health protection, determination of exposition limits and prevention of diseases caused by deficiency of trace elements. Concentrations of the named elements in urine of the Czech population were determined by means of atomic absorption spectrometry. The urine has been collected during 1996-2000 from 1192 individuals (816 males and 376 females, average age 34.6 years) and 2008 children (1052 boys and 956 girls, average age 9.9 years). Mineralization in a microwave digestion system was used in sample preparation. The accuracy of results was checked by means of the Control Materials Seronorm 403,125 and BioRad 69,041. Values of concentrations of the trace elements in urine found for adult (medians) were 0.36 microgram Cd.g-1 creatinine, 10.6 micrograms Cu.g-1 creatinine, 0.68 microgram Hg.g-1 creatinine, 3.3 micrograms Pb.g-1 creatinine, 6.2 micrograms Se.g-1 creatinine, and 397 micrograms Zn.g-1 creatinine, respectively. Statistically significant differences between men and women have been found in the concentrations of Cu and Hg. In the juvenile population following concentrations have been found: 0.29 microgram Cd.g-1 creatinine, 16.1 micrograms Cu.g-1 creatinine, 0.32 microgram Hg.g-1 creatinine, 4.8 micrograms Pb.g-1 creatinine, 10.2 micrograms Se.g-1 creatinine and 460 micrograms Zn.g-1 creatinine. Statistically significant differences between boys and girls were found only in Cu and Hg concentrations. Concentrations of the studied elements correspond to the published values concerning population not exposed professionally.
Keywords: olovo; Lead; Copper; Male; Česká republika; Child; rtuť; Deficiency Diseases; dítě; Adult; Selenium; Mercury; dospělí; mužské pohlaví; referenční hodnoty; Czech Republic; Reference Values; selen; lidé; kovy; ženské pohlaví; Humans; karenční nemoci; zinek; Metals; měď; spektrofotometrie atomová; kadmium; Female; Zinc; Spectrophotometry, Atomic; Cadmium